2003
DOI: 10.1002/nvsm.198
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying the inclination to donate to particular types of charity

Abstract: Two hundred and fifty members of the general public were interviewed in central London and asked to assume that they had been given a certain sum of money, all of which they had to donate to a single good cause. The interviewees were presented with the names of three organisations in different fields (cancer care, animal welfare and human rights) and asked to make a selection. Respondents were then questioned about their personal values, inclinations and other characteristics potentially relevant to the choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
192
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(221 citation statements)
references
References 18 publications
6
192
0
11
Order By: Relevance
“…In attracting donors, NPOs' target marketing tends to be unfocused and even sporadic. And although individuals are often very specific in choosing NPOs to which to donate (Bennett, 2003(Bennett, , 2006, even regular donors or wealthy patrons limit their contributions in hard economic times (Katz, 2005). It is essential that NPOs understand what specifically motivates individuals to donate to a particular charity or category of charities.…”
Section: Discussion Developing a Nonprofit Marketing Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In attracting donors, NPOs' target marketing tends to be unfocused and even sporadic. And although individuals are often very specific in choosing NPOs to which to donate (Bennett, 2003(Bennett, , 2006, even regular donors or wealthy patrons limit their contributions in hard economic times (Katz, 2005). It is essential that NPOs understand what specifically motivates individuals to donate to a particular charity or category of charities.…”
Section: Discussion Developing a Nonprofit Marketing Strategymentioning
confidence: 99%
“…These board volunteers are also generally passionate about the NPO's cause, but they can be reluctant to make tough decisions when needed (Katz, 2005). One study found that only 17% of NPO executives thought that their board of directors was effective (Jansen & Kilpatrick, 2005 In one study, Bennett (2003) found clear evidence that both personal values and demographic factors such as age, income, and education influence individual choices about which charities to support. Surprisingly, he did not find personal experience to be a universal determinate in donation behavior.…”
Section: The Npo Volunteermentioning
confidence: 99%
“…Interestingly, within the literature little attention is given to the differences in employee engagement based on the type of CSR initiative. Both corporate fundraising (CF) and corporate volunteering (CV) have been addressed individually, with researchers examining employee motivations and volunteering (e.g., Gary et al 2010;Muthuri et al 2009;Pajo and Lee 2011;Peterson 2004b) and mechanisms that drive charitable giving (e.g., Bekkers and Wiepking 2011;Bennett 2003). However, employee engagement is affected by the type of initiative and thus examining differences in engagement for corporate volunteering and corporate fundraising provides critical insight into antecedents to both CSR engagement and disengagement and subsequently forms a key contribution of this research.…”
Section: Intervention Designmentioning
confidence: 99%
“…These considerations have been termed Value Sensitive Design (VSD) by Friedman [14], who refers to: ownership and property; privacy, freedom from bias, universal usability, trust, autonomy, informed consent and identity. This is contrasted with sociology and social psychology where values are criteria that are used to evaluate or make judgements about events or people encountered, helping explain individual and collective behaviour [6]. As social interactions become increasingly mediated by technology then these two interpretations of values merge and in doing so, they govern user action or non-action within technology [18].…”
Section: Values and Value Sensitive Concernsmentioning
confidence: 99%